Mejoramiento del control automático de dos equipos del laboratorio de operaciones y procesos unitarios de la Facultad de Ingeniería Química de la Universidad Nacional de la Amazonía Peruana-2023 - Gómez Bardales, Hadryan Corainne (2024)
The general objective of the present work of thesis was: accomplishing the improvement of two teams ‘automatic control of the Laboratory of Operations and Unitary Processes of the FIQ UNAP-2023, for which, firstly, Zelio Soft2 V5.4.2 investigated about the surroundings and the programming language of the software of simulation himself. The two teams were: prototype with logical programmable control to automate the passage of time of functioning of four electrobombas and equipmen to determine the relation between the dynamic height and the flow in electrobombas peripheral. Straightaway, became elaborate the intervening logic circuit which the functioning of the five electrobombas could get under control from a PC. At a later time, the improvement of the automatic control of the aforementioned teams came true, by means of the design and frame-up of a system of automation. Finally, the aforementioned system got settled in the mentioned equipment, coming true correspondingly and in good shape simultaneous the following operations: four electric pumps alternation and whiled away the time of an electric pump. The results obtained in the seven-performance testings of the system of automation, indicated that the residue of the passage of time of functioning of the five electrobombas, it is zero, demonstrating this way than timers 1, 2, 3 and 4 of the PLC (logical programmable control), have an efficiency of 100, because the aforementioned electrobombas did not present any delays when caught fire and becoming extinguished, according to what's programmed in the logic circuit. This way, it has come true with the realistic general, trying on at the same time his general hypothesis